Changes in Spina Bifida Lesion Level After Folic Acid Fortification in the US. Issue 4 (April 2023) - Mai, Cara T.; Evans, Jane; Alverson, Clinton J.; Yue, Xin; Flood, Timothy; Arnold, Kathryn; Nestoridi, Eirini; Denson, Lindsay; Adisa, Olufunmilola; Moore, Cynthia A.; Nance, Amy; Zielke, Katherine; et al.
ABSTRACT: In 1992, the US Public Health Service recommended that all women capable of becoming pregnant should consume 400 μg of folic acid daily to decrease the risk of neural tube defects (ie, spina bifida and anencephaly). The year 1998 brought mandated folic acid fortification of cereal products within the United States, following which a substantial decline in neural tube defects at birth occurred. Studies also have suggested that lesion levels in cases of spina bifida are directly affected by folic acid fortification. Locations of such lesions contribute to outcome and prognosis of the condition. When compared with sacral and lower lumbar lesions, the greatest risks of disability and mortality are associated with cervical, thoracic, and high lumbar lesions. Individuals with thoracic or high lumbar lesions require a wheelchair and orthosis in adulthood for ambulation 70% to 99% of the time. As lesion levels therefore determine function and overall quality of life, assessment of whether folic acid fortification significantly impacts lesion levels is important. This study aimed to examine patterns of lesion levels in spina bifida following mandatory folic acid fortification in the United States. A call was issued by the National Birth Defects Prevention Network for State Birth Defects Programs' spina bifida lesion data before and after fortification mandate. To be eligible, programs needed to provide verbatim medical record text descriptions of spina bifida diagnoses. The 6 participating programs were from the states of Arizona, California (covering 8 counties), Oklahoma, South Carolina, Utah, and metropolitan Atlanta (Georgia). Birth years examined included the prefortification years of 1992–1996 and the postfortification period of 1999–2016. Central processing and analysis occurred as each program provided case-level data (deidentified) based on the exclusion/inclusion criteria to the Centers for Disease Control and Prevention. Medical and record text description of the spina bifida diagnosis and codes were the basis of case information, using the International Classification of Diseases, Ninth Edition, Clinical Modification or the Centers for Disease Control and Prevention and Prevention/British Pediatric Association coding system. Types of spina bifida included in the study were spinal rachischisis, myelomeningocele/meningomyelocele, meningocele, and spina bifida not otherwise specified. Cases excluded were cranial lesions, lipomyelomeningocele/lipomeningomyelocele, dysraphism related to split cord malformations, and spina bifida occulta. Lesion-level information was provided based on the highest lesion using nonradiographic clinical assessment. Classification of severe upper-level lesions included cervical or thoracic lesion-level cases, whereas lower-level lesions included cases with lumbar or sacral. The study defined open lesion as leaking spinal fluid or membrane covered only, whereas closed lesions were defined as having intact-skin covering and lacking fluid leakage. Spina bifida cases were considered isolated when no other anomalies related to the primary cause of abnormal neural tube closure were present (nor were secondary to the neurologic complications caused by it). Examining associations between fortification period and the outcomes (lesion level and spina bifida) occurred using the generalized estimating approach to logistic (case severity analyses) and log-linear (PR analyses) regression, which accounted for clustering of cases by state. From a total of 7, 816, 062 live births, 2593 cases of spina bifida met the case inclusion criteria. Overall, 573 cases were included in the prefortification period (birth prevalence of 4.07 per 10, 000 live births), and 2020 cases were included in the postfortification period (birth prevalence of 3.15 per 10, 000 live births). Overall, 80.2% of cases resulted in live births, and most cases of spina bifida involved lower-level lesions (81.3%). Most lesions were lumbar, and the proportions prefortification and postfortification were 61.4% and 72.0%, respectively, with a higher proportion of lumbar lesions seen in the postfortification period. The odds of upper-level to lower-level lesions decreased by 70% after fortification. The spina bifida live birth prevalence decreased significantly and remained consistently low throughout the early, mid, and recent postfortification periods. The study found a 72% decrease overall in prevalence of severe, upper-level lesions following mandatory folic acid fortification in the United States. The limitations of the study include the shortcomings of relying on diagnostic codes, the difficulty of coding lesion level using the International Classification of Diseases, Ninth Edition, Clinical Modification coding scheme, the lack of recorded functional outcome for children in medical records (indirect indicators of severity), the lack of preconception and prenatal folic acid data, and the possible variation of case ascertainment within programs contributing studies. A major study strength is its potential to address additional important questions regarding epidemiology and spina bifida. The classification of spinal defects is complex, and this study adds to the limited distribution data that exist for prefortification and postfortification subtypes. The study concluded that the overall prevalence of severe upper-level lesions in spina bifida cases experienced a steep reduction following mandatory folic acid fortification institution within the United States, whereas no change in the prevalence of less severe lower-level lesions took place. Additional examinations are warranted to better understand the magnitude and mechanism of spina bifida severity in relation to folic acid intake.